Institutional anomie theory and gambling-related crime: An empirical test in Macau - Dai, Mengliang (Journal of criminology, 2023)
To date, scholars have rarely applied institutional anomie theory to gambling-related crime. Using time series data on the rates of illegal gambling, money laundering, organised crime, and drug-related crime, as well as various indicators of the economy and noneconomic social institutions, this study tested the applicability of institutional anomie theory to gambling-related crime. The study found that unemployment positively related to organised crime and drug-related crime. GDP per capita is positively associated with illegal gambling crime, organised crime, and drug-related crime. However, all social institutional variables failed to predict gambling-related crime. Moreover, for the interaction effects, this finding also provided limited and mixed support for the theory. The implications of these findings are discussed.